2016
DOI: 10.1016/j.cobeha.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 influences food and drug reward

Abstract: Natural rewards, including food, water, sleep and social interactions, are required to sustain life. The neural substrates that regulate the reinforcing effects of these behaviors are also the same neurobiological mechanisms mediating mood, motivation and the rewarding effects of pharmacological stimuli. That the neuropeptide glucagon-like peptide-1 (GLP-1) is under investigation for both the homeostatic and hedonic controls of feeding is not surprising or novel. However, if the neural substrates that underlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 44 publications
9
50
0
1
Order By: Relevance
“…GLP-1R agonists suppress reward-directed behavior towards both food and drugs of abuse [38,83]. With respect to cocaine, Exendin-4 decreases cocaine-induced locomotion, conditioned place preference and self-administration [3537,39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GLP-1R agonists suppress reward-directed behavior towards both food and drugs of abuse [38,83]. With respect to cocaine, Exendin-4 decreases cocaine-induced locomotion, conditioned place preference and self-administration [3537,39].…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1Rs are located throughout the brain [91]. Importantly, they are found in the VTA, which receives direct projections for GLP-1 producing neurons of the nucleus of the solitary tract [32], and can be targeted selectively to reduce motivated behavior for food and drug reward (see [38,83,92] for review). In support of this hypothesis, a recent study has demonstrated a reduction in cocaine self-administration behavior by intra-VTA agonism of GLP-1Rs [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Мезолимбическая система награды участвует в формировании алкогольной, никотиновой, наркотической зависимости. Изучаются перспективы те-рапии, основанной на эффектах ГПП-1, для лечения дан-ных состояний [25].…”
Section: влияние эндогенного гпп-1 на аппетит и массу телаunclassified
“…For example, glucagon-like peptide-1 (GLP-1), an incretin hormone, has been shown to regulate both food and drug reinforcement [171]. With regard to nicotine addiction, systemic administration of a GLP-1 receptor agonist attenuates nicotine-induced increases in extracellular dopamine levels in the NAc and reduces the rewarding properties of nicotine [172].…”
Section: Neurotransmitter Mechanisms Regulating Nicotine Seekingmentioning
confidence: 99%